2015
DOI: 10.1007/978-94-017-9652-1_7
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Magnetic Fabric in Layered Mafic-Ultramafic Intrusions

Abstract: Anisotropy of magnetic susceptibility (AMS) has been recognised as a well-established fabric analysis tool for intrusive igneous rocks since the 1990s. The AMS technique provides directional information for magnetic foliation and magnetic lineation fabric components of the AMS ellipsoid, potentially coupled with a quantification of the overall fabric strength and geometry. The magnetic susceptibility (and therefore the AMS) of igneous rocks is often dominated by ferromagnetic mineral phases such as magnetite o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 104 publications
0
14
0
Order By: Relevance
“…We suggest that the porphyritic peridotite layers such as that illustrated in Figure 4j are harrisite sills that underwent shearing within the crystal mush, causing fragmentation of the large skeletal crystals within the hot tears and shear zones (see Hepworth et al, 2017), and producing the strong foliations that characterise both the megacrysts and groundmass olivine. O'Driscoll et al (2015) showed that the porphyritic peridotites also exhibit a well-developed olivine lineation, supporting the idea that a component of simple shear was involved in fabric development. The consistency of thickness of the porphyritic peridotite layers might mean that this process is only important where the sill is thin, where magma-static pressure is overcome by shear stress, where the inflation rate (or flux rate) in the sill is too low.…”
Section: Syn-magmatic Reworking Of Harrisite In Deforming Crystal Mushmentioning
confidence: 54%
See 1 more Smart Citation
“…We suggest that the porphyritic peridotite layers such as that illustrated in Figure 4j are harrisite sills that underwent shearing within the crystal mush, causing fragmentation of the large skeletal crystals within the hot tears and shear zones (see Hepworth et al, 2017), and producing the strong foliations that characterise both the megacrysts and groundmass olivine. O'Driscoll et al (2015) showed that the porphyritic peridotites also exhibit a well-developed olivine lineation, supporting the idea that a component of simple shear was involved in fabric development. The consistency of thickness of the porphyritic peridotite layers might mean that this process is only important where the sill is thin, where magma-static pressure is overcome by shear stress, where the inflation rate (or flux rate) in the sill is too low.…”
Section: Syn-magmatic Reworking Of Harrisite In Deforming Crystal Mushmentioning
confidence: 54%
“…Unlike the fine-grained olivine crystals, the megacrysts contain abundant crystallographically-constrained skeletal magnetite inclusions (Fig. 10a, b) (see also O'Driscoll et al 2015). In the porphyritic peridotite, these inclusions only occur in the olivine megacrysts (i.e., they are absent in the fine-grained olivine in the granular-textured peridotite).…”
Section: Porphyritic Peridotitementioning
confidence: 98%
“…The application of other quantitative textural techniques to layered intrusions is also flourishing. Crystal size distributions and methods of quantifying crystal alignment such as electron backscatter diffraction (EBSD) and anisotropy of magnetic susceptibility (AMS; O'Driscoll et al 2015) are examples of such investigative tools. The power of these techniques, especially when combined, as well as their potential to future research is illustrated in the article by Cheadle and Gee (this issue).…”
Section: Current Contoversies and New Developmentsmentioning
confidence: 99%
“…Charlier et al, 2015). Nevertheless, magnetic fabric studies in mafic -ultramafic intrusions are relatively rare (O'Driscoll et al, 2015). A possible reason for this is that interpreting magnetic fabrics in mafic rocks can be complicated by the presence of oriented ferromagnetic inclusions in mafic silicates .…”
Section: Introductionmentioning
confidence: 99%